Perspektif Socio-Legal dalam Tradisi Lomban dan Melarung Kepala Kerbau di Pantai Jepara Jawa Tengah - -, Mashudi (Faculty of Sharia and Law Universitas Islam Nahdlatul Ulama, 2025)
Cultural clashes that often occur in society do not always have a negative impact on the roles and functions of social life. Events that are sometimes perceived as mystical and contradictory to the noble values of Islamic law frequently arise and require clarification to dispel long-standing assumptions. The Lomban tradition, involving the sea-floating of a buffalo head by the fishing communities of Jepara Regency, serves as an example of how Islamic law can coexist with local traditions to foster a harmonious and peaceful society—forming the foundation for national unity. The diverse religious understandings within Jepara society, as described above, can contribute to regional income through the tourism sector and therefore deserve to be preserved. This study aims to present the perspective of Islamic law regarding the practice of sea-floating a buffalo head during the Lomban Syawalan festival by Jepara’s fishing communities, and to formulate a responsive and solution-oriented approach for sustaining Islamic legal culture, empowering local communities, and supporting economic development through tourism. Using a socio-legal approach, along with the principles of ‘urf (customary tradition), maslahah (public interest), and legal-social transformation, the study finds that the practice of sea-floating a buffalo head during the Syawalan festival is not, in substance, contrary to the comprehensive concept of Islamic law, nor can it be categorized as shirk (idolatry). Rather, the tradition reflects the fishermen’s gratitude to Allah SWT and their desire to share prosperity with fellow creatures. A responsive and constructive Islamic legal formulation of this tradition has the potential to unite religious diversity and generate foreign exchange. This local wisdom, through the development of an Islamic legal-cultural model around the buffalo head floating ritual, can be preserved within modern society undergoing value shifts.